Canadian Stroke Best Practice Recommendations: secondary prevention of stroke guidelines, update 2014. Issue 3 (23rd December 2014) - Coutts, Shelagh B.; Wein, Theodore H.; Lindsay, M. Patrice; Buck, Brian; Cote, Robert; Ellis, Paul; Foley, Norine; Hill, Michael D.; Jaspers, Sharon; Jin, Albert Y.; Kwiatkowski, Brenda; MacPhail, Carolyn; et al.
Abstract : Every year, approximately 62 000 people with stroke and transient ischemic attack are treated in Canadian hospitals. The 2014 update of the Canadian Secondary Prevention of Stroke guideline is a comprehensive summary of current evidence‐based recommendations for clinicians in a range of settings, who provide care to patients following stroke. Notable changes in this 5th edition include an emphasis on treating the highest risk patients who present within 48 h of symptom onset with transient or persistent motor or speech symptoms, who need to be transported to the closest emergency department with capacity for advanced stroke care; a recommendation for brain and vascular imaging (of the intra‐ and extracranial vessels) to be completed urgently using computed tomography/computed tomography angiography; prolonged cardiac monitoring for patients with suspective cardioembolic stroke but without evidence for atrial fibrillation on electrocardiogram or holter monitoring; and de‐emphasizing the need for routine echocardiogram. The C anadian   S troke   B est   P ractice   R ecommendations include a range of supporting materials such as implementation resources to facilitate the adoption of evidence to practice, and related performance measures to enable monitoring of uptake and effectiveness of the recommendations using a standardized approach. The guidelines further emphasize the need for a systems approach to stroke care, involving an interprofessional team, with access to specialists regardless of patient location, and the need to overcome geographical barriers to ensure equity in access within a universal health‐care system.